1975
DOI: 10.1111/j.1600-0560.1975.tb00828.x
|View full text |Cite
|
Sign up to set email alerts
|

Lichen Sclerosus et Atrophicus An Electron Microscopic Study

Abstract: The ultrastructural changes in seven cases of lichen sclerosus et atrophicus are described. An interesting epidermal alteration was the presence of collagen fibrils in the intercellular space; furthermore, the basal cells were altered by condensation and homogenization of the tonofibrils. The basement membrane was not uniform and often multilayered. The anchoring fibrils were numerous. In the cutis intertwining strands of fine filaments, bundles of immature collagen and normal collagen could be found. In liche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…This suggests other structural defects besides the lack of elastic fibers in the upper dermis in LSA. Relative to this, Kint and Geerts (17) found collagen fibrils in the epidermal intercellular spaces as Mann and Cowan (18) had observed and suggested that the dermoepidermal junction in LSA was not normal. They (17) also observed that: "the elastin fibers were rare" in the upper dermis in LSA.…”
Section: Commentmentioning
confidence: 80%
“…This suggests other structural defects besides the lack of elastic fibers in the upper dermis in LSA. Relative to this, Kint and Geerts (17) found collagen fibrils in the epidermal intercellular spaces as Mann and Cowan (18) had observed and suggested that the dermoepidermal junction in LSA was not normal. They (17) also observed that: "the elastin fibers were rare" in the upper dermis in LSA.…”
Section: Commentmentioning
confidence: 80%
“…A study of early histopathological changes in LS revealed loss of elastic fibers in 100% of cases, suggesting that it is an early finding 7 . Most electron microscopic studies on LS confirm the decrease in elastic fibers within the homogenized zone 5,20–23 . However, the underlying cause or mechanism behind the decrease and loss of elastic fibers is not known.…”
Section: Discussionmentioning
confidence: 99%
“…58 Other EM changes that have been reported include abnormalities in the basement membrane zone and condensation of tonofilaments in the basal epidermal cells. 59 Associations A variety of dermatological and systemic disorders have been associated with LS. Systemic conditions associated with LS include diabetes mellitus, 60 thyroid diseases, 61 systemic lupus erythematosus, 62 systemic sclerosus and CREST syndrome, 63 primary biliary cirrhosis, 64 polymyalgia rheumatica, 65 prolactinoma, 66 pernicious anaemia 67 and chronic hepatitis C infection.…”
Section: Epidemiologymentioning
confidence: 99%